MXene composite material as well as preparation method and application thereof
By using MXene composite material in the lithium sulfur battery separator and combining the covalent connection between the anthraquinone-based covalent organic frame and the aminated MXene, the problem of the lithium sulfur battery separator being unable to suppress the lithium polysulfide shuttle effect and safety during the charging and discharge process is solved, and the efficient cycle stability and safety of the battery are achieved.
Patent Information
- Application Number
- CN202411583685.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing lithium-sulfur battery separators cannot effectively suppress the shuttle effect of lithium polysulfide during charging and discharging, resulting in rapid attenuation of battery capacity. At the same time, the metal lithium negative electrode has the risk of dendrites piercing the separator, resulting in safety problems.
MXene composite material is used, which forms a material with high conductivity and rich lithium-philic sites by covalently connecting anthraquinone-based covalent organic frame with aamide MXene to form a material with high conductivity and abundant lithium-philic sites, used to modify the separator to synergistically catalyze the redox reaction of polysulfides.
It effectively suppresses the shuttle effect of lithium polysulfide, improves the cycle stability and rate performance of lithium-sulfur batteries, and at the same time, by improving the conductivity and lithium-philicity of the separator, the risk of dendrites is reduced and the safety of the battery is improved.
Smart Images

Figure CN119613919A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials, and particularly relates to an MXene composite material, a preparation method thereof and an application thereof. Background Art
[0002] Lithium-sulfur batteries (Li-S) are considered to be one of the next-generation new high-energy-density battery systems with the most development potential due to their high theoretical energy density (2600 Wh·kg -1 ) and the high natural abundance of sulfur element. However, their commercial progress is still restricted in many aspects. On the one hand, there are complex multiphase reactions in the positive electrode of lithium-sulfur batteries, and there is a large reaction energy barrier in the liquid-solid conversion, resulting in a slow sulfur redox kinetic process. At present, the wide-distribution pore structure of commercial polyolefin separators cannot inhibit the shuttle effect of soluble polysulfides (LiPSs) (Li2S x , 2 < x ≤ 8) during charge and discharge, resulting in rapid attenuation of battery capacity. On the other hand, metallic lithium as the negative electrode material is an inevitable choice to match the high discharge capacity of sulfur, but there are still serious safety problems such as lithium dendrite growth piercing the separator, leading to battery short circuit and even combustion and explosion.
[0003] Based on the above background, introducing a functional coating that can inhibit the shuttle effect on the positive electrode side of the lithium-sulfur battery separator is considered an effective strategy. However, the initially introduced materials such as carbon nanotubes, graphene, and porous aerogels as functional coatings, although having good conductivity and high specific surface area, cannot further accelerate the sulfur redox kinetics. Researchers have further introduced transition metal-based compounds with electrocatalytic activity into the functional coating. These catalysts are usually compounded with materials with high specific surface area and have abundant active sites, which anchor and catalytically convert polysulfides through strong interactions to accelerate the sulfur redox kinetic process. However, the transition metal-based compound hybrid materials lack lithiophilic sites and are difficult to achieve uniform lithium ion transport to inhibit the growth of lithium dendrites. Covalent organic frameworks (COFs) have the advantages of light weight, adjustable structure, high specific surface area, excellent chemical and thermodynamic stability, etc. In the research work of functional modified coatings for lithium-sulfur batteries, it has been proved that adsorbing or repelling polysulfides through the electrostatic interaction between the unique porous properties of COFs and specific functional groups is one of the effective strategies to inhibit the polysulfide shuttle effect. In addition, thanks to the ordered pores and adjustable structural units, the COF functional modified coating can provide a lithium ion transport channel with a large number of lithiophilic groups. However, the intrinsic conductivity of COFs is poor and the utilization rate of polysulfide active components is low, which limits their improvement of the specific capacity of lithium-sulfur batteries. Summary of the Invention
[0004] In order to overcome at least one of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a MXene composite material, which composites MXene with a covalent organic framework (COFs) material so that the two can synergistically exert an adsorption-catalytic function, thereby solving the technical problems of poor cycle stability and poor rate performance of lithium-sulfur batteries caused by the poor intrinsic conductivity of COFs materials.
[0005] A second object of the present invention is to provide a method for preparing the above-mentioned MXene composite material.
[0006] A third object of the present invention is to provide a modified diaphragm.
[0007] A fourth object of the present invention is to provide a lithium-sulfur battery.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] A first aspect of the present invention provides a MXene composite material, comprising an anthraquinone-based covalent organic framework and an amino-modified MXene; the anthraquinone-based covalent organic framework is covalently connected to the surface of the amino-modified MXene.
[0010] Furthermore, the anthraquinone-based covalent organic framework is covalently linked to the amino groups of the amino-modified MXene.
[0011] In the present invention, MXene is a two-dimensional inorganic compound mainly composed of transition metal carbides.
[0012] Preferably, the raw materials for preparing the anthraquinone-based covalent organic framework include diaminoanthraquinone (DAAQ) and trialdehyde phloroglucinol (TFP).
[0013] Preferably, the diaminoanthraquinone comprises 2,6-diaminoanthraquinone 2,7-Diaminoanthraquinone or 1,5-diaminoanthraquinone At least one of; further preferably, the diaminoanthraquinone is selected from 2,6-diaminoanthraquinone.
[0014] Preferably, the mass ratio of the diaminoanthraquinone to the trialdehyde phloroglucinol is 1:(0.3-1.5); more preferably 1:(0.4-1.2); and even more preferably 1:(0.5-1).
[0015] Preferably, the raw materials for preparing the aminated MXene include diazonium salt and MXene.
[0016] Preferably, the aminated MXene is prepared by a method comprising the following steps: subjecting a diazonium salt and MXene to an amination reaction to prepare the aminated MXene.
[0017] Preferably, the temperature of the amination reaction is -5 to 5°C; more preferably -2 to 2°C; and even more preferably 0°C.
[0018] Preferably, the amination reaction is carried out in water.
[0019] Preferably, the diazonium salt is selected from 4-aminobenzene diazonium salt.
[0020] The second aspect of the present invention provides a method for preparing a MXene composite material, comprising the following steps: mixing amino MXene, diaminoanthraquinone (DAAQ), trialdehyde pyrosorbin (TFP) and a solvent, and performing a solvothermal reaction to obtain the MXene composite material as described in the first aspect of the present invention.
[0021] Preferably, the temperature of the solvothermal reaction is 100 to 140°C; more preferably 105 to 135°C; and even more preferably 110 to 130°C.
[0022] Preferably, the solvent thermal reaction time is 48 to 96 hours; more preferably 54 to 90 hours; and even more preferably 60 to 84 hours.
[0023] Preferably, the solvent comprises at least one of glacial acetic acid, N,N-dimethylacetamide (DMAC) or mesitylene; further preferably, the solvent comprises glacial acetic acid, N,N-dimethylacetamide and mesitylene.
[0024] Preferably, in the solvent, the volume ratio of glacial acetic acid, N,N-dimethylacetamide and mesitylene is 1:(5-10):(1-5); more preferably, it is 1:(7-8):(2-3).
[0025] Preferably, the ratio of the total mass of the diaminoanthraquinone and the trialdehyde phloroglucinol to the mass of the amino MXene is 1:(0.3-3); more preferably 1:(0.4-2); and even more preferably 1:(0.5-1).
[0026] Preferably, the ratio of the amino MXene to the solvent is 1 mg: (0.1-1) mL; more preferably 1 mg: (0.2-0.8) mL; and even more preferably 1 mg: (0.3-0.5) mL.
[0027] The third aspect of the present invention provides a modified diaphragm, comprising a base layer and a functional coating disposed on the base layer; the raw materials for preparing the functional coating include the MXene composite material described in the first aspect of the present invention.
[0028] Preferably, the raw materials for preparing the functional coating further include a binder, a conductive agent and an organic solvent.
[0029] Preferably, the binder includes at least one of polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, carboxymethyl cellulose, polymethyl methacrylate, styrene-butadiene rubber or polyvinyl alcohol; further preferably, the binder includes at least one of polyvinylidene fluoride, polyacrylic acid or polyacrylonitrile; further preferably, the binder is selected from polyvinylidene fluoride (PVDF).
[0030] Preferably, the conductive agent includes at least one of conductive carbon black, acetylene black, carbon nanotubes or graphene; further preferably, the conductive agent is selected from conductive carbon black (Super P).
[0031] Preferably, the organic solvent comprises at least one of N,N-dimethylformamide, N-methylpyrrolidone, acetone or tetrahydrofuran; further preferably, the organic solvent is selected from N,N-dimethylformamide (NMP).
[0032] Preferably, the mass ratio of the MXene composite material to the binder is 1:(0.05-1); more preferably 1:(0.08-0.8); and even more preferably 1:(0.1-0.6).
[0033] Preferably, the mass ratio of the MXene composite material to the conductive agent is 1:(0.05-0.5); more preferably 1:(0.08-0.4); and even more preferably 1:(0.1-0.3).
[0034] Preferably, the thickness of the functional coating is 1 to 10 μm; more preferably, 2 to 8 μm; further preferably, 3 to 5 μm.
[0035] Preferably, the material of the base layer includes at least one of metal, carbon material or polymer material; further preferably, the material of the base layer includes at least one of aluminum, copper, carbon cloth or polyolefin; further preferably, the material of the base layer is selected from polyolefin.
[0036] Preferably, the polyolefin comprises at least one of polypropylene, polyethylene or a polypropylene-polyethylene composite material; further preferably, the polyolefin is selected from polypropylene (PP).
[0037] The fourth aspect of the present invention provides a lithium-sulfur battery, comprising a positive electrode, a negative electrode and a battery separator arranged between the positive electrode and the negative electrode; the raw material for preparing the battery separator comprises the MXene composite material described in the first aspect of the present invention, or the battery separator is the modified separator described in the third aspect of the present invention.
[0038] The beneficial effects of the present invention are as follows: the present invention obtains a MXene composite material by covalently connecting an anthraquinone-based covalent organic framework and an amino MXene. On the one hand, the covalent connection between the covalent organic framework and the MXene can reduce the electron transfer energy barrier, thereby improving the utilization rate of the redox active groups in the covalent organic framework; on the other hand, MXene can not only improve the overall conductivity of the material, but also anchor and catalyze the conversion of polysulfides through active metal sites, and the anthraquinone groups in the anthraquinone-based covalent organic framework can be bound by lithium bonds and converted into lithium polysulfide. Therefore, the MXene composite material provided by the present invention can achieve the synergistic catalysis of the double-end binding sites, effectively solving the problem of poor intrinsic conductivity of the covalent organic framework, and the MXene composite material is conducive to the preparation of lithium-sulfur batteries with excellent electrochemical performance.
[0039] Specifically, compared with the prior art, the present invention has the following advantages:
[0040] 1. The anthraquinone-based covalent organic framework has a microporous structure, which is conducive to the adsorption of polysulfides, limiting the shuttle effect, and achieving synergistic adsorption-catalytic performance; in addition, the anthraquinone-based covalent organic framework has an ordered pore structure and abundant lithium-philic sites (such as carbonyl, ketoamine bond and anthraquinone group, etc.), which are conducive to promoting efficient and uniform lithium ion transport.
[0041] 2. The present invention performs amination treatment on MXene so that the anthraquinone-based covalent organic framework can be covalently connected to the surface of the amination MXene, thereby achieving a good composite effect. The obtained MXene composite material is made into a lithium-sulfur battery, which can achieve excellent electrochemical cycle performance and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 SEM images of MXene and DAAQ-TFP / MXene-1.
[0043] Figure 2 Nitrogen adsorption-desorption curves and pore size distribution diagram of DAAQ-TFP / MXene-1 and DAAQ-TFP.
[0044] Figure 3 UV-visible absorption curves of MXene, DAAQ-TFP / MXene-1, DAAQ-TFP and blank group solutions.
[0045] Figure 4 The physical picture and SEM picture of DAAQ-TFP / MXene-1@PP.
[0046] Figure 5 Cyclic voltammetry curves and electrochemical impedance spectra of DAAQ-TFP / MXene-1@PP, DAAQ-TFP@PP, MXene@PP and PP separators.
[0047] Figure 6 This is a comparison chart of the rate performance tests of DAAQ-TFP / MXene-1@PP, DAAQ-TFP@PP, MXene@PP and PP diaphragms.
[0048] Figure 7 This is a comparison chart of the long-cycle performance of DAAQ-TFP / MXene-1@PP, DAAQ-TFP@PP, MXene@PP and PP separators. DETAILED DESCRIPTION
[0049] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.
[0050] Covalent organic framework preparation example
[0051] A DAAQ-TFP material, the specific preparation method is as follows:
[0052] DAAQ (13.5 mg), TFP (7.9 mg), DMAC (4.5 mL), mesitylene (1.5 mL), and glacial acetic acid solution (6 M, 0.6 mL) were added to a custom glass tube. After ultrasonic treatment for about 15 minutes, the glass tube was quickly frozen at 77 K, and then three freeze-degase-thaw cycles were performed, and the glass tube was flame-sealed. After the temperature returned to room temperature, the reaction was heated at 120 ° C for 72 hours. After the solvent was removed by filtration under reduced pressure, the product was washed three times with DMF and then washed three times with acetone. After washing, the remaining product was placed in a vacuum oven and dried at 60 ° C to completely remove the solvent to obtain DAAQ-TFPCOF material.
[0053] Composite material example 1
[0054] This embodiment provides a MXene composite material, recorded as DAAQ-TFP / MXene-1, and the specific preparation method is as follows:
[0055] S1: 1,4-phenylenediamine (542 mg, 5.0 mmol) was added to a round-bottom flask and 40 mL of deionized water was added, and the minimum amount of hydrochloric acid solution required for dissolution was added dropwise. The resulting solution was kept at 0 °C in a low-temperature reaction tank. Subsequently, 10 mL of an aqueous solution containing 335 mg of NaNO2 (5.0 mmol) was quickly added dropwise within 20 minutes under stirring. The prepared 4-aminobenzenediazonium salt aqueous solution was slowly dripped into 100 mL of an aqueous dispersion containing 300 mg of MXene under stirring at 0 °C. After the mixture reacted overnight, the solvent was removed by centrifugation and then washed with anhydrous ethanol and water in sequence, and the product was separated by centrifugation. After freeze-drying overnight, amino MXene nanosheets (MXene-NH2) were obtained.
[0056] S2: Aminated MXene nanosheets (21 mg), DAAQ (13.5 mg), TFP (7.9 mg), DMAC (4.5 mL), mesitylene (1.5 mL), and glacial acetic acid (6 M, 0.6 mL) were added to a custom glass tube. After ultrasonic treatment for about 15 minutes, the glass tube was quickly frozen at 77 K, and then three freeze-degase-thaw cycles were performed, and the glass tube was flame-sealed. After the temperature returned to room temperature, the reaction was heated at 120 ° C for 72 hours. After the solvent was removed by filtration under reduced pressure, the product was washed three times with DMF and then washed three times with acetone. After washing, the remaining product was placed in a vacuum oven and dried at 60 ° C to completely remove the solvent to obtain DAAQ-TFP / MXene-1.
[0057] Composite material example 2
[0058] This embodiment provides a MXene composite material, recorded as DAAQ-TFP / MXene-2, and the specific preparation method is as follows:
[0059] S1: 1,4-phenylenediamine (542 mg, 5.0 mmol) was added to a round-bottom flask and 40 mL of deionized water was added, and the minimum amount of hydrochloric acid solution required for dissolution was added dropwise. The resulting solution was kept at 0 °C in a low-temperature reaction tank. Subsequently, 10 mL of an aqueous solution containing 335 mg of NaNO2 (5.0 mmol) was quickly added dropwise within 20 minutes under stirring. The prepared 4-aminobenzenediazonium salt aqueous solution was slowly dripped into 100 mL of an aqueous dispersion containing 300 mg of MXene under stirring at 0 °C. After the mixture reacted overnight, the solvent was removed by centrifugation and then washed with anhydrous ethanol and water in sequence, and the product was separated by centrifugation. After freeze-drying overnight, amino MXene nanosheets (MXene-NH2) were obtained.
[0060] S2: Aminated MXene nanosheets (21 mg), DAAQ (27 mg), TFP (15.8 mg), DMAC (4.5 mL), mesitylene (1.5 mL), and glacial acetic acid (6 M, 0.6 mL) were added to a custom glass tube. After ultrasonic treatment for about 15 minutes, the glass tube was quickly frozen at 77 K, and then three freeze-degase-thaw cycles were performed, and the glass tube was flame-sealed. After the temperature returned to room temperature, the reaction was heated at 120 ° C for 72 hours. After the solvent was removed by filtration under reduced pressure, the product was washed three times with DMF and then washed three times with acetone. After washing, the remaining product was placed in a vacuum oven and dried at 60 ° C to completely remove the solvent to obtain DAAQ-TFP / MXene-2.
[0061] Modified diaphragm example 1
[0062] This embodiment provides a modified diaphragm, which is denoted as DAAQ-TFP / MXene-1@PP. The specific preparation method is as follows:
[0063] 24 mg DAAQ-TFP / MXene-1 (prepared in Composite Material Example 1), 3 mg PVDF, and 3 mg SuperP were mixed and ground thoroughly, and NMP was slowly dripped and continued to grind until the slurry showed metallic luster. The slurry was scraped onto a diaphragm (Celgard2325) with a 50 μm scraper and vacuum dried at 60°C to obtain a DAAQ-TFP / MXene-1@PP modified diaphragm.
[0064] Modified diaphragm example 2
[0065] This embodiment provides a modified diaphragm, which is denoted as DAAQ-TFP / MXene-2@PP. The specific preparation method is as follows:
[0066] 24 mg DAAQ-TFP / MXene-2 (prepared in Composite Material Example 2), 3 mg PVDF, and 3 mg SuperP were mixed and ground thoroughly, and NMP was slowly dripped and continued to grind until the slurry showed metallic luster. The slurry was scraped onto a diaphragm (Celgard2325) with a 50 μm scraper and vacuum dried at 60°C to obtain a DAAQ-TFP / MXene-2@PP modified diaphragm.
[0067] Modified diaphragm example 3
[0068] This embodiment provides a modified diaphragm, which is denoted as DAAQ-TFP / MXene-3@PP. The specific preparation method is as follows:
[0069] 24 mg DAAQ-TFP / MXene-1 (prepared in Example 1 of the composite material), 12 mg PVDF, and 4 mg SuperP were mixed and ground thoroughly, and NMP was slowly dripped and continued to grind until the slurry showed metallic luster. The slurry was scraped onto a diaphragm (Celgard2325) with a 50 μm scraper and vacuum dried at 60°C to obtain a DAAQ-TFP / MXene-3@PP modified diaphragm.
[0070] Modified diaphragm comparative example 1
[0071] This comparative example provides a modified diaphragm, which is recorded as DAAQ-TFP@PP. The specific preparation method is as follows:
[0072] 24 mg DAAQ-TFP, 3 mg PVDF and 3 mg SuperP were mixed and ground thoroughly, and NMP was slowly added and ground continuously until the slurry showed metallic luster. The slurry was scraped onto a diaphragm (Celgard2325) with a 50 μm scraper and vacuum dried at 60 °C to obtain DAAQ-TFP@PP modified diaphragms.
[0073] Modified diaphragm comparative example 2
[0074] This comparative example provides a modified diaphragm, which is denoted as MXene@PP. The specific preparation method is as follows:
[0075] 24 mg MXene, 3 mg PVDF and 3 mg SuperP were mixed and ground thoroughly, and NMP was slowly dripped in and ground continuously until the slurry showed metallic luster. The slurry was scraped onto the diaphragm (Celgard2325) with a 50 μm scraper and vacuum dried at 60 °C to obtain MXene@PP modified diaphragms.
[0076] Performance Characterization
[0077] 1) Morphological characterization of MXene composites
[0078] The morphology of DAAQ-TFP / MXene-1 prepared from MXene and composite material Example 1 was characterized, and the results were Figure 1 shown. Figure 1 SEM images of MXene and DAAQ-TFP / MXene-1, where a is the SEM image of MXene; b is the SEM image of DAAQ-TFP / MXene-1.
[0079] according to Figure 1 It can be seen from a that MXene materials have a typical two-dimensional flake morphology with a relatively flat and smooth surface; Figure 1As can be seen from figure b, in the DAAQ-TFP / MXene-1 material, there are obvious COF nanoparticles on the surface of the MXene nanosheets.
[0080] 2) Nitrogen desorption experiment and pore size distribution test of MXene composites
[0081] Nitrogen desorption experiments and pore size distribution tests were performed on DAAQ-TFP / MXene-1 prepared in Composite Material Example 1 and DAAQ-TFP prepared in Covalent Organic Framework Preparation Example. Figure 2 Nitrogen desorption curves and pore size distribution diagrams of DAAQ-TFP / MXene-1 and DAAQ-TFP, where a is the nitrogen desorption curve and b is the pore size distribution diagram.
[0082] according to Figure 2 Based on the gas adsorption data in a, the specific surface areas of DAAQ-TFP / MXene-1 and DAAQ-TFP were calculated to be 761.4 m 2 g -1 and 1154.3m 2 g -1 ;according to Figure 2 As can be seen from figure b, DAAQ-TFP / MXene-1 and DAAQ-TFP have similar pore structures, and the main pore sizes are concentrated at 1.9nm and 4.8nm. A large number of micropores can quickly adsorb lithium polysulfide, and the abundant mesopores are conducive to the rapid transmission of lithium ions.
[0083] 3) Lithium polysulfide adsorption test of MXene composites
[0084] Li2S6 adsorption experiments were conducted to directly compare the adsorption-catalytic performance of the materials. Lithium polysulfide adsorption tests were performed on MXene, DAAQ-TFP / MXene-1 prepared in Composite Material Example 1, and DAAQ-TFP prepared in Covalent Organic Framework Preparation Example. The results are as follows Figure 3 As shown, Li2S6 represents the blank group solution.
[0085] Figure 3 UV-visible absorption curves of MXene, DAAQ-TFP / MXene-1, DAAQ-TFP and blank group solutions.
[0086] from Figure 3 It can be seen that compared with the absorbance of the characteristic peak of Li2S6 at 400nm of the blank group solution, the peak intensity of the solution with DAAQ-TFP / MXene-1 almost disappeared, which proves the great advantage of DAAQ-TFP / MXene-1 in adsorption-catalytic performance.
[0087] 4) Morphological characterization of modified diaphragm
[0088] The morphology of DAAQ-TFP / MXene-1@PP prepared in Example 1 of the modified diaphragm was characterized, and the results were Figure 4 shown. Figure 4 These are the physical pictures and SEM pictures of DAAQ-TFP / MXene-1@PP, where a is the physical picture of DAAQ-TFP / MXene-1@PP; b is the cross-sectional SEM picture of DAAQ-TFP / MXene-1@PP; c is the SEM picture of the top surface of DAAQ-TFP / MXene-1@PP; d is the SEM picture of the bottom surface of DAAQ-TFP / MXene-1@PP.
[0089] according to Figure 4 It can be seen from a that DAAQ-TFP / MXene-1 is evenly distributed on the PP separator; according to Figure 4 From b to d, it can be seen that in DAAQ-TFP / MXene-1@PP, on the top surface with the modified coating, DAAQ-TFP / MXene-1 forms a macroscopically dense modified coating with a thickness of about 3 μm; while the bottom surface without the scraped material still retains the original morphology of the PP diaphragm.
[0090] 2) Cyclic voltammetry and electrochemical impedance spectroscopy of modified diaphragms
[0091] DAAQ-TFP / MXene-1@PP prepared in Example 1 of the modified diaphragm, DAAQ-TFP@PP prepared in Comparative Example 1 of the modified diaphragm, MXene@PP prepared in Comparative Example 2 of the modified diaphragm, and PP diaphragm were assembled into a lithium-sulfur battery, wherein the side with the modified coating was facing the sulfur positive electrode. -1 The cyclic voltammetry curves (CV curves) and electrochemical impedance spectroscopy of the Li-S batteries based on the four separators were tested under the condition of a voltage window of 1.7 to 2.8 V.
[0092] Figure 5 Cyclic voltammetry curves and electrochemical impedance spectra of DAAQ-TFP / MXene-1@PP, DAAQ-TFP@PP, MXene@PP and PP separators, where a is the cyclic voltammetry curve and b is the electrochemical impedance spectra. Figure 5From a, we can see that the lithium-sulfur battery assembled with DAAQ-TFP / MXene-1@PP has the highest peak current, and there is an obvious positive shift in the reduction peak potential and a negative shift in the oxidation peak potential, indicating that the lithium-sulfur battery assembled with DAAQ-TFP / MXene-1@PP has a faster redox kinetic process. The above results fully prove that DAAQ-TFP / MXene-1@PP can reduce battery polarization and catalyze the redox reaction of polysulfides. According to Figure 5 It can be seen from b that the lithium-sulfur battery assembled with DAAQ-TFP / MXene-1@PP has the smallest charge transfer impedance, indicating that it significantly enhances the process of charge transfer and ion diffusion.
[0093] 3) Rate performance test of modified diaphragm
[0094] DAAQ-TFP / MXene-1@PP prepared in modified membrane Example 1, DAAQ-TFP@PP prepared in modified membrane Comparative Example 1, MXene@PP prepared in modified membrane Comparative Example 2, and PP membrane were assembled into a lithium-sulfur battery, wherein the side with the modified coating was facing the sulfur positive electrode. Rate performance tests were performed at different current densities.
[0095] Figure 6 This is a comparison chart of the rate performance test of DAAQ-TFP / MXene-1@PP, DAAQ-TFP@PP, MXene@PP and PP diaphragms. Figure 6 It can be seen that the Li-S battery assembled with DAAQ-TFP / MXene-1@PP has the highest average specific capacity at 0.1, 0.2, 0.5, 1, 2, 3, and 5C rates.
[0096] 4) Long cycle test of modified diaphragm
[0097] DAAQ-TFP / MXene-1@PP prepared in modified membrane Example 1, DAAQ-TFP@PP prepared in modified membrane Comparative Example 1, MXene@PP prepared in modified membrane Comparative Example 2, and PP membrane were assembled into a lithium-sulfur battery, wherein the side with the modified coating was facing the sulfur positive electrode. A long cycle test was carried out at a current density of 1C.
[0098] Figure 7 This is a comparison chart of the long cycle performance of DAAQ-TFP / MXene-1@PP, DAAQ-TFP@PP, MXene@PP and PP diaphragms. Figure 7 It can be seen that DAAQ-TFP / MXene-1@PP has the highest first-cycle discharge specific capacity and the lowest average capacity decay rate per cycle. The results show that DAAQ-TFP / MXene-1@PP has excellent cycle performance.
[0099] The anthraquinone-based covalent organic framework prepared in the embodiment of the present invention has a microporous structure, which is conducive to the adsorption of polysulfides, restricts the shuttle effect, and achieves synergistic adsorption-catalytic performance; in addition, the ordered pore structure and rich lithium-philic sites (such as carbonyl, ketoamine bond and anthraquinone group, etc.) of the anthraquinone-based covalent organic framework are conducive to promoting efficient and uniform lithium ion transmission. In addition, in the embodiment of the present invention, by amination treatment of MXene, the anthraquinone-based covalent organic framework can be covalently connected to the surface of the amination MXene, achieving a good composite effect, and the obtained MXene composite material is made into a lithium-sulfur battery, which can achieve excellent electrochemical cycle performance and rate performance.
[0100] In summary, the present invention obtains a MXene composite material by covalently connecting an anthraquinone-based covalent organic framework and an amino MXene. On the one hand, the covalent connection between the covalent organic framework and the MXene can reduce the electron transfer energy barrier, thereby improving the utilization rate of the redox active groups in the covalent organic framework; on the other hand, MXene can not only improve the overall conductivity of the material, but also anchor and catalyze the conversion of polysulfides through active metal sites, and the anthraquinone groups in the anthraquinone-based covalent organic framework can be bound by lithium bonds and converted into lithium polysulfide. Therefore, the MXene composite material provided by the present invention can achieve the synergistic catalysis of the double-end binding sites, effectively solve the problem of poor intrinsic conductivity of the covalent organic framework, and the MXene composite material is conducive to the preparation of lithium-sulfur batteries with excellent electrochemical performance.
Claims
1. A MXene composite material, characterized in that: It includes an anthraquinone-based covalent organic framework and an amino-modified MXene; the anthraquinone-based covalent organic framework is covalently connected to the surface of the amino-modified MXene.
2. The MXene composite material according to claim 1, characterized in that The raw materials for preparing the anthraquinone-based covalent organic framework include diaminoanthraquinone and trialdehyde phloroglucinol; Preferably, the diaminoanthraquinone includes at least one of 2,6-diaminoanthraquinone, 2,7-diaminoanthraquinone or 1,5-diaminoanthraquinone; and / or the mass ratio of the diaminoanthraquinone to the trialdehyde phloroglucinol is 1:(0.3-1.5).
3. The MXene composite material according to claim 1, characterized in that The raw materials for preparing the amino MXene include diazonium salt and MXene.
4. A method for preparing a MXene composite material, characterized in that: The following steps are involved: The aminated MXene, diaminoanthraquinone, trialdehyde phloroglucinol and a solvent are mixed and subjected to a solvothermal reaction to obtain the MXene composite material as claimed in any one of claims 1 to 3.
5. The preparation method according to claim 4, characterized in that: The temperature of the solvent thermal reaction is 100-140°C; And / or, the solvent thermal reaction time is 48 to 96 hours.
6. The preparation method according to claim 4, characterized in that: The solvent includes at least one of glacial acetic acid, N,N-dimethylacetamide or mesitylene; And / or, the ratio of the total mass of the diaminoanthraquinone and the trialdehyde phloroglucinol to the mass of the amino MXene is 1:(0.3-3).
7. A modified diaphragm, characterized in that: It comprises a base layer and a functional coating arranged on the base layer; the raw material for preparing the functional coating comprises the MXene composite material according to any one of claims 1 to 3.
8. The modified diaphragm according to claim 7, characterized in that: The raw materials for preparing the functional coating also include a binder, a conductive agent and an organic solvent; Preferably, the binder comprises at least one of polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, carboxymethyl cellulose, polymethyl methacrylate, styrene-butadiene rubber or polyvinyl alcohol; and / or, the conductive agent comprises at least one of conductive carbon black, acetylene black, carbon nanotubes or graphene; and / or, the organic solvent comprises at least one of N,N-dimethylformamide, N-methylpyrrolidone, acetone or tetrahydrofuran; and / or, the mass ratio of the MXene composite material to the binder is 1:(0.05-1); And / or, the mass ratio of the MXene composite material to the conductive agent is 1:(0.05-0.5).
9. The modified diaphragm according to claim 7, characterized in that: The material of the base layer includes at least one of metal, carbon material or polymer material.
10. A lithium-sulfur battery, characterized in that: It comprises a positive electrode, a negative electrode and a battery separator arranged between the positive electrode and the negative electrode; the raw material for preparing the battery separator comprises the MXene composite material described in any one of claims 1 to 3, or the battery separator is selected from the modified separator described in any one of claims 7 to 9.
Citation Information
Patent Citations
Carbon fiber surface grafted two-dimensional network structure reinforced polyether-ether-ketone composite material and preparation method thereof
CN112457629A
Application of MoS2-Mo2C MXene composite material in preparation of lithium-sulfur battery diaphragm
CN117293482A
Lithium-sulfur battery preparation method based on hydroxyl amination covalent organic framework diaphragm
CN117673654A
Anthraquinone-imine polymer as well as synthesis method and application thereof
CN118440318A
Cited By
Preparation method of disperse black 9 compound
CN120118534A
A preparation method of disperse black 9 compound
CN120118534B